PERKEMBANGAN MIKROGAMETOFIT DAN UJI VIABILITAS SERBUK SARI KELAPA (Cocos nucifera L. “Ancak”) - Cerli Tonika Sari, Ni Luh Gede; Kriswiyanti, Eniek; Darsini, Ni Nyoman (SIMBIOSIS; Vol I, No 2, Tahun 2013)
The research observed the type of pollen shape, development of microgametophyte, and pollen viability of Cocos nucifera L. “Ancak”, that is the pollen structure Cocos nucifera L. used preparation with acetolysis method. Development of microgametophyte, and pollen viability with germinated pollen in vitro used 0,8% of agar media in sugar solution 0%, 50%, and 70%. The result showed that the type of pollen shape Cocos nucifera L. “Ancak”: circular, sulkus, media, Subferoidal, P/E: (1.12-1.18). Development of microgametophyte Cocos nucifera L. “Ancak” the flowers are ripe generally at the level of uninucleate (> 60%) and binukleat (<40%). Male gametes (trinukleat) started on day 2,4. percentage of pollen viability in vitro low average (< 2.5%). Keywords: Pollen structure, microgametophyte, viability test, in vitro